Economic burden associated with inadequate antidepressant medication management among patients with depression and known cardiovascular diseases: insights from a United States–based retrospective claims database analysis. (3rd March 2020) - Bangalore, Sripal; Shah, Ruchitbhai; Gao, Xin; Pappadopulos, Elizabeth; Deshpande, Chinmay G.; Shelbaya, Ahmed; Prieto, Rita; Stephens, Jennifer; Chambers, Richard; Schepman, Patricia; McIntyre, Roger S.
Abstract: Aims: The current study examined the association between insufficient major depressive disorder (MDD) care and healthcare resource use (HCRU) and costs among patients with prior myocardial infarction (MI) or stroke. Methods: This was a retrospective study conducted using the MarketScan Claims Database (2010–2015). The date of the first MI/stroke diagnosis was defined as the cardiovascular disease (CVD) index date and the first date of a subsequent MDD diagnosis was the index MDD date. Adequacy of MDD care was assessed during the 90 days following the index MDD date (profiling period) using 2 measures: dosage adequacy (average fluoxetine equivalent dose of ≥20 mg/day for nonelderly and ≥10 mg/day for elderly patients) and duration adequacy (measured as the proportion of days covered of 80% or higher for all MDD drugs). Study outcomes included all-cause and CVD-related HCRU and costs which were determined from the end of the profiling period until the end of study follow-up. Propensity-score adjusted generalized linear models (GLMs) were used to compare patients receiving adequate versus inadequate MDD care in terms of study outcomes. Results: Of 1, 568 CVD patients who were treated for MDD, 937 (59.8%) were categorized as receiving inadequate MDD care. Results from the GLMs suggested that patients receiving inadequate MDD care had 14% more all-cause hospitalizations, 4% more all-cause outpatient visits, 17% more CVD-related outpatient visits, 13% more CVD-related emergency room (ER) visits, higher per patient per year CVD-related hospitalization costs (21, 485 vs. 17, 756), higher all-cause outpatient costs (2, 820 vs. 2, 055), and higher CVD-related outpatient costs (520 vs. 434) compared to patients receiving adequate MDD care. Limitations: Clinical information such as depression severity and frailty, which are potential predictors of adverse CVD outcomes, could not be ascertained using administrative claims data. Conclusions: Among post-MI and post-stroke patients, inadequate MDD care was associated with a significantly higher economic burden.